Long-term adjustable gastric band with resultant megaoesophagus causing cardiac compression. Issue 12 (31st December 2021) - De Silva, Ramesh; Pham, My; Devadas, Michael; Kiat, Hosen
Abstract: Oesophageal dilatation following laparoscopic-assisted gastric banding (LAGB) is a well-described complication reported in up to 80% of LAGB patients [ 1, 2 ]. Severe oesophageal dilatation in addition to aperistalsis is known as megaoesophagus. Symptomatic compression cardiac compression from oesophageal dilatation as a complication of LAGB is an extremely rare complication and is presented in this case report.